Gambaran Personal Hygiene dan Sanitasi Industri Rumah Tangga Produksi Tahu di Wilayah Kapas, Kabupaten Bojonegoro - Nazahah Hunafa; Narwati Narwati; Winarko Winarko (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Personal hygiene of food handlers at tofu production IRTPs in the Cotton Area is known to not use PPE, smoke in the workplace, and pack directly by hand. The purpose of this study was to describe personal hygiene and sanitation for the home industry of tofu production in the Kapas Region, Bojonegoro Regency. This type of research is descriptive, with a population of all home industries producing tofu in the Cotton Region as many as 5 IRTPs. The test parameters were Escherichia coli on the palm swab sample of the handler and MPN Coliform on the tofu soaked water source sample. Data were analyzed descriptively. The results showed that the personal hygiene of the handlers was in sufficient category (47.69%). Industrial sanitation conditions are categorized as sufficient (44%). The swab results of 5 samples of the handlers' palms were all negative for Escherichia coli and the tofu soaking water source did not exceed the maximum limit of the MPN Coliform parameter as many as 3 industries.Keywords: personal hygiene; household food industry sanitation; Escherichia coli; MPN ColiformABSTRAK Personal hygiene penjamah makanan di IRTP produksi tahu di Wilayah Kapas diketahui tidak menggunakan APD, merokok di tempat kerja, dan pengemasan langsung dengan tangan. Tujuan penelitian ini adalah menggambarkan personal hygiene dan sanitasi industri rumah tangga produksi tahu di Wilayah Kapas, Kabupaten Bojonegoro. Jenis penelitian ini adalah deskriptif, dengan populasi seluruh industri rumah tangga produksi tahu di Wilayah Kapas sejumlah 5 IRTP. Parameter uji berupa Escherichia coli pada sampel swab telapak tangan penjamah dan MPN Coliform pada sampel sumber air rendaman tahu. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa personal hygiene penjamah berkategori cukup (47,69%). Kondisi sanitasi industri berkategori cukup (44%). Hasil swab 5 sampel telapak tangan penjamah seluruhnya adalah negatif Escherichia coli dan sumber air rendaman tahu dalam keadaan tidak melebihi batas maksimum parameter MPN Coliform sebanyak 3 industri.Kata kunci: personal hygiene; sanitasi industri rumah tangga pangan; Escherichia coli; MPN Coliform